First of all, we must multiply each equation by a suitable number in order to get the same ** leading coefficient. **In simple terms, we must make the coefficient of the x or the y in both equations the same. So here it is easy to multiply the first equation by 3 to get 6x+9y=24 and the second by 2 which gives us 6x+4y=14. Now if we subtract equation 1 by equation 2, we have 5y=10. To make y the subject, we must divide both sides by 5 which gives us y=2.Let us substitute this value of y into 2x+3y=8. We have 2x+(3*2)=8. Again if we rearrange this for x, we have x=1.